Applied extreme value statistics - Kinnison, Robert R. (Battelle Press, 1984)
"An extension, revision, and compilation of a series of tutorial papers prepared for limited distribution to radioecologists as TRAN-STAT issues 14-18"--P. vii.Includes index.Bibliography: p. 139-145